Morphometric Variations in the Grasshopper, Chromacris speciosa from Two Localities of Pernambuco in Northeastern Brazil - Cisneiros, Roberta Araújo (University of Wisconsin Library, 2012)
The present study describes morphometric variations in the grasshopper, Chromacris speciosa (Thunberg, 1824) (Orthoptera: Acridoidea: Romaleidae) from two locations in the state of Pernambuco, Brazil. The distance between the sites chosen for collections (Recife and São Lourenço da Mata) is approximately 16 km. The investigation was based on a comparative study of external morphological characteristics of the grasshoppers. Morphometric measurements took into account the different body parts and appendages. Statistical analysis of the measurements revealed significant differences in the size of the specimens between the two locations. Homogeneity tests of the covariance and equality matrices between mean vectors of the results revealed that the grasshopper populations in Recife and São Lourenço da Mata are distinctly different. These findings provide morphological evidence for intraspecific variation in morphological characteristics of the C. speciosa populations from the two locations.